Inovasi Pelayanan Pembayaran Pajak Bumi Dan Bangunan Di Kabupaten Garut - Lia Juliasih; Yusuf Hermawan; Andi Gunawan (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2022)
AbstractLand and Building tax in Garut Regency faces some barriers suc as a lack of taxpayers awareness and innovation. To overcome these problems, the United Nations payment innovation was carried out to improve the quality of service. This study aims to find out about how PBB payment innovations through payment points in Garut Regency and what factors influence the success of the innovations carried out. The concept used in this study is Mulgan and Albury's theory which states that successful innovations can be seen from service product innovation, service process innovation, service method innovation, policy innovation, and system innovation. The method used in this research is descriptive research method with a qualitative approach. The location of this research is the Regional Revenue Agency (BAPENDA) of Garut Regency. Data obtained by using literature studies and field studies in the form of observation, interviews and documentation studies. The results of this study indicate that the innovations carried out successfully were seen from service product innovations, process service method, policy, and system carried out by adding PPOB in the payment system, but need further development and socialization to perfect this innovation. Factors that influence this success are the existence of regulations, budget support, good human resources and the presence of digital technology. This innovation needs to be developed to increase taxpayer awareness and service quality